2000
DOI: 10.1054/bjoc.2000.1512
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of neoadjuvant chemotherapy in oropharyngeal carcinoma

Abstract: Patients with head and neck cancer represent 11% of the malignant tumours diagnosed in French males (Ménégoz et al, 1998). While most small tumours can be cured, a majority of the tumours are advanced and despite progress in surgery and radiotherapy, the prognosis remains poor. In the past years, systemic chemotherapy has been used in an attempt to improve the results of loco-regional treatment. Clinical trials have shown a high response rate with a combination of Cisplatinum (CDDP) and 5 Fluoro-Uracil (5FU) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(67 citation statements)
references
References 6 publications
2
65
0
Order By: Relevance
“…Induction chemotherapy has an established role of organ preservation in the treatment of patients with laryngeal and hypopharyngeal primary tumors and has been studied as a route to achieve organ preservation in other head and neck sites. [1][2][3][4][5][6] The most frequently used radiation schedule after induction therapy has been daily treatment at a dose of 1.8 -2.0 Gy per day up to a total dose of 65-70 Gy, although other schedules have been used. This approach has yielded acceptable results overall in terms of functional preservation, although the outcome for patients who do not respond well to induction treatment has not been good.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction chemotherapy has an established role of organ preservation in the treatment of patients with laryngeal and hypopharyngeal primary tumors and has been studied as a route to achieve organ preservation in other head and neck sites. [1][2][3][4][5][6] The most frequently used radiation schedule after induction therapy has been daily treatment at a dose of 1.8 -2.0 Gy per day up to a total dose of 65-70 Gy, although other schedules have been used. This approach has yielded acceptable results overall in terms of functional preservation, although the outcome for patients who do not respond well to induction treatment has not been good.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Phase III studies have demonstrated the efficacy of combined chemotherapy and radiation for maintaining a functional larynx for patients with either a laryngeal or hypopharyngeal primary tumor without altering survival and for improving survival in patients with unresectable disease. 1,[3][4][5][6] Patients who do not have a significant response to the first two cycles of chemotherapy frequently go directly to surgery or radiation therapy. A common finding in these trials is that patients who achieve a primary site clinical and/or pathologic complete response (CR) to three cycles of induction chemotherapy fare well in terms of local disease control.…”
mentioning
confidence: 99%
“…Despite advances in our understanding of the biology of this disease, improvements in surgical and radiation therapy techniques, and the additional impact of chemotherapy and combined-modality approaches, longterm survival in patients with locally advanced disease, measured as 2-year and 3-year overall survival (OS) and progression free survival, has remained Ͻ 50% in randomized trials. [2][3][4][5] Combination chemotherapy with cisplatin and fluorouracil (PF) is the most commonly used induction regimen in the treatment of patients with locally advanced SCCHN. The original PF chemotherapy regimen results in major response rates of 60 -90% and complete responses (CRs) in the range of 20 -50%.…”
mentioning
confidence: 99%
“…3,4,6 PF is an effective alternative to surgery in patients with carcinoma of the larynx and hypopharynx who are treated for organ preservation. [2][3][4][5] Induction chemotherapy with PF also has shown improved survival in patients with both unresectable and resectable disease when chemotherapy was followed by standard fractionated radiotherapy and when postradiation surgery for lymph node disease was included in the treatment. 2,6 It should be noted, however, that this is not a generally accepted approach and does not represent the standard of care.…”
mentioning
confidence: 99%
“…This was presumably from micrometastatic disease that local therapy or lower dose chemotherapy as part of chemoradiation would not adequately treat. This theoretical argument has been tested in several trials that have been unable to show a consistent survival benefit Schuller et al, 1988;Paccagnella et al, 1994;El-Sayed and Nelson 1996;Domenge et al, 2000;Pignon et al, 2000). (Table 4a).…”
Section: An Evolving Role For Induction Chemotherapymentioning
confidence: 99%